Structure-based redesign of docking domain interactions modulates the product spectrum of a rhabdopeptide-synthesizing NRPS. Issue 1 (December 2018) - Hacker, Carolin; Cai, Xiaofeng; Kegler, Carsten; Zhao, Lei; Weickhmann, A.; Wurm, Jan; Bode, Helge; Wöhnert, Jens
Abstract Several peptides in clinical use are derived from non-ribosomal peptide synthetases (NRPS). In these systems multiple NRPS subunits interact with each other in a specific linear order mediated by specific docking domains (DDs), whose structures are not known yet, to synthesize well-defined peptide products. In contrast to classical NRPSs, single-module NRPS subunits responsible for the generation of rhabdopeptide/xenortide-like peptides (RXPs) can act in different order depending on subunit stoichiometry thereby producing peptide libraries. To define the basis for their unusual interaction patterns, we determine the structures of all N-terminal DDs (N DDs) as well as of anN DD-C DD complex and characterize all putative DD interactions thermodynamically for such a system. Key amino acid residues for DD interactions are identified that upon their exchange change the DD affinity and result in predictable changes in peptide production. Recognition rules for DD interactions are identified that also operate in other megasynthase complexes. Rhabdopeptides are synthesized by non-ribosomal peptide synthetases (NRPSs) and the multiple NRPS subunits interact through docking domains (DD). Here the authors provide insights into DD interaction patterns and present the structures of three N-terminal docking domains (N DD) and aN DD-C DD complex and derive a set of recognition rules for DD interactions.